Study on Factors Influencing Performance of The Best Baitul Maal Wat Tamwils [BMTS] In Indonesia - Muhammad Akhyar Adnan; Agus Widarjono; M.Bekti Hendri Anto (Jurnal Iqtisad, 2003)
The Islamic financial institutions generally, and the Islamic banks particularly have been interesting phenomena for about last two or three decades. They are believed [by many] to be an interesting, challenging and promising model of the current or conventional financial systems. In the case of Indonesia, despite of the fact that there are two official types of Islamic bank, as they are accommodated by Banking Act No. 7 1992, as well as Banking Act No. 10 1998, there is an additional type as what so-called Baitul Maal wat Tamwil, or abbreviated as BMT.BMTs have even attracted more attention. First, because they are generally unregistered under the normal practice rule such as Central Bank. Second, they have developed very significantly in quantity and spread in very wide areas of different provinces. Currently, there are about two thousand BMTs around the country. This indicates that BMTs have been contributing to the national economy. Third, although the country is hit by the crisis, many BMTs operate smoothly. This is contrary to what might be seen in the fact faced by many formal conventional banks. Based on the above factors, we are interested in investigating what the influencing factors are behind the good performance of BMTs in general. This is the main objective of this study. To answer the research problems, the data were collected from the best 47 BMTs in five different provinces, i.e., West Java, Jakarta Special Territory of Capital, Middle Java, Special Region of Yogyakarta, and East Java. The simple descriptive, as well as the regression analysis, was applied. It is found that there are four main influencing factors. They are the salary rate of management, the education and the management skill of personnel's involved in daily operation and the product attributes. Other factors predicted at the beginning [such as working hours, the number of products] are found to have a negative correlation to the BMT's performance. One important implication of these finding is that there is a serious need to improve the management skill as well as the need to refine the managers' rate of salary.Keywords: Islamic Financial Institutions, Microfinance, Performance evaluation.